States’ Attitude to International Boundaries and Africa’s Challenging Integration: CUES from Pre-1945 Europe (Journal of International Studies, 2018)
Since the 1960s, African states have sought ways to overcome the challenges of economic and political integration through the establishment and promotion of regional and subregional organizations across the continent. The different efforts have yielded very modest success altogether. However, it appears that Africans are the architect of the continentâ€™s low level of integration. Africaâ€™s nationalist approach to international boundaries coupled with the inclination and disposition towards economic nationalism with regards to neighbouring states has been identified as the major impediments to the process of integration in the continent. By adopting content analysis approach, this paper explores the nexus between the stateâ€™s attitude to international boundaries and regional integration. This paper analyses how Europeanâ€™s attitude to international boundaries and the resulting trans-boundary cooperation between and among the different groups of European states before 1945 was instrumental to the historic success of integration in post-1945 Europe. It further looks into the pre-1945 European experience with trans-boundary cooperation as a template for assessing trans-boundary cooperation among African states during the colonial and post-colonial periods. This paper concludes that modest achievements so far recorded in the process of regional integration in Africa is a function of the nationalistic attitude of states to international boundary. Subsequently, the study recommends that to achieve real integration in the continent, Africans and their leaders must change their attitude towards inherited colonial boundaries from their prevailing official postures as lines of divides to more liberal disposition as corridors of cooperation.